MENAKAR ARGUMENTASI YURIDIS-PASTORAL KEBIJAKAN USKUP DIOSESAN DALAM MEMBATASI LAYANAN SAKRAMEN PADA MASA PANDEMI COVID -19 - Rikardus Jehaut (STIPAS St. Sirilus Ruteng, 2022)
The purpose of the present article is to analyse the juridical and pastoral basis behind the policy on the limitation of sacramental service for the faithful introduced by Diocesan Bishop as the Church’s authority in the face of the spreading COVID -19 epidemic. The analysis aims to answer questions not only concerning the conformity of the policy with the Code of Canon law 1983, but also pertaining the issue of the rights of the faithful to receive sacrament. In relation to these questions, the author concludes that the introduction of the policy was adequate and necessary for the sake of the salvation of body of the people as a whole and in accord with the Church’s law. On the other hand, the author also point out that the above-mentioned policy must be always carried out properly without ignoring the rights of the faithful. Therefore, the article postulates that it is very important for the Diocesan Bishop to maintain a rational balance between the salvation of body of the people as a whole and Christ’s faithful’s rights to receive sacraments from the Church.